Determinants of farm-level adoption of cultural practices for banana xanthomonas wilt control in Uganda - Jogo, W.; Karamura, E.B.; Tinzaara, William; Kubiriba, Jerome; Rietveld, Anne M. (Canadian Center of Science and Education, 2013)
Understanding the factors influencing farmers’adoption decisions of the disseminated Banana Xanthomonas wilt (BXW) control package is critical for successful management of the disease. This paper analysed the determinants of farmers’ decisions to adopt the control package by smallholder banana farmers in Uganda. A binomial Logit model is applied to household survey data collected from 350 households. Results from the study show that household labour availability, technology pack age attributes such as labour demand and perceived effectiveness of the practices in managing the disease; and agro-ecological location and banana production system significantly influence adoption decisions. These results suggest the need for adaptation of the technology package to better suit the needs and socio-economic conditions of smallholder farmers through a farmer participatory technology development approach that takes into account research findings, farmers’ indigenous knowledge and resource constraints to enhance adoption.